Di‐ and triphenylacetate complexes of yttrium and europium. Issue 7 (23rd June 2016) - Minyaev, Mikhail E.; Vinogradov, Alexandr A.; Roitershtein, Dmitrii M.; Lyssenko, Konstantin A.; Ananyev, Ivan V.; Nifant'ev, Ilya E.
Abstract : The X‐ray structures of the non‐isomorphic [Eu(Ph2 CHCOO)3 (dme)]2 and [Y(Ph2 CHCOO)3 (dme)]2 complexes (dme is 1, 2‐dimethoxyethane) exhibit three coordination modes of the anionic diphenylacetate ligands. The {[Eu(Ph3 CCOO)3 (CH3 OH)4 ]·2CH3 OH}2 dimer, formed by intermolecular O—H…O hydrogen bonds via two bridging methanol molecules, displays two types of triphenylacetate ligand coordination. Abstract : The significant variety in the crystal structures of rare‐earth carboxylate complexes is due to both the large coordination numbers of the rare‐earth cations and the ability of the carboxylate anions to form several types of bridges between rare‐earth metal atoms. Therefore, these complexes are represented by mono‐, di‐ and polynuclear complexes, and by coordination polymers. The interaction of LnCl3 (thf) x (Ln = Eu or Y; thf is tetrahydrofuran) with sodium or diethylammonium diphenylacetate in methanol followed by recrystallization from a DME/THF/hexane solvent mixture (DME is 1, 2‐dimethoxyethane) leads to crystals of the non‐isomorphic dinuclear complexes tetrakis(μ‐2, 2‐diphenylacetato)‐κ 4 O : O ′;κ 3 O, O ′: O ′;κ 3 O : O, O ′‐bis[(1, 2‐dimethoxyethane‐κ 2 O, O ′)(2, 2‐diphenylacetato‐κ 2 O, O ′)europium(III)], [Eu(C14 H11 O2 )6 (C4 H10 O2 )2 ], (I), and tetrakis(μ‐2, 2‐diphenylacetato)‐κ 4 O : O ′;κ 3 O, O ′: O ′;κ 3 O : O, O ′‐bis[(1, 2‐dimethoxyethane‐κ 2 O, O ′)(2, 2‐diphenylacetato‐κ 2 O, O ′)yttrium(III)], [Y(C14 H11 O2 )6 (C4 H10 O2 )2 ], (II), possessing monoclinic ( P 21 / c ) symmetry. The [Ln(Ph2 CHCOO)3 (dme)]2 molecule (Ln = Eu or Y) lies on an inversion centre and exhibits three different coordination modes of the diphenylacetate ligands, namely bidentate κ 2 O, O ′‐terminal, bidentate μ2 ‐κ 1 O :κ 1 O ′‐bridging and tridentate μ2 ‐κ 1 O :κ 2 O, O ′‐semibridging. The terminal and bridging ligands in (I) are disordered over two positions, with an occupancy ratio of 0.806 (2):0.194 (2). The interaction of EuCl3 (thf)2 with Na[Ph3 CCOO] in methanol followed by crystallization from hot methanol produces crystals of tetrakis(methanol‐κ O )tris(2, 2, 2‐triphenylacetato)‐κ 4 O : O ′;κ O ‐europium(III) methanol disolvate, [Eu(C19 H15 O2 )3 (CH3 OH)4 ]·2CH3 OH, (III)·2MeOH, with triclinic ( P ) symmetry. The molecule of (III) contains two O, O ′‐bidentate and one O ‐monodentate terminal triphenylacetate ligand. (III)·2MeOH possesses one intramolecular and four intermolecular hydrogen bonds, forming a [(III)·2MeOH]2 dimer with two bridging methanol molecules.